Microstructure-dependent etching behavior of a partially recrystallized Invar alloy. (May 2022) - Park, Sung Jin; Jo, Seong-Hyeon; Oh, Sehyeok; Oh, Young-Seok; Kim, Se-Jong; Lee, Ho Won; Kang, Seong-Hoon; Hoon Moon, Young; Jung, Jaimyun
Graphical abstract: Highlights: The microstructure of an Invar alloy heavily influences the etching behavior of the alloy. Surface energy, geometrically necessary dislocations (GNDs), and grain boundary density are directly proportional to etching rate. The effect of GNDs is less distinguished for grains with very small GND density values. Abstract: Due to their low coefficient of thermal expansion, Invar sheets are used as the material for fine metal masks (FMM). In producing theses masks, the sheets are often chemically etched to produce arrays of micro-holes. Because etching behavior of a material depends not only on the chemical composition of the material, but also on the surface microstructure of the material, an in depth exploration on the role of the surface microstructure of an Invar alloy on the etching behavior of the alloy is fundamental in manufacturing high quality FMMs. In this study, microstructure dependent etching behavior of a partially recrystallized Invar sheet is investigated. The Invar alloy was partially recrystallized at 750℃ to examine how recrystallized and non-crystallized grains differ in their etching behaviors using electron backscatter diffraction (EBSD) and atomic force microscope (AFM) techniques. The results show that the overall etching behavior of the partially recrystallized Invar sheet not only depends on the properties of individual grains such as orientation dependent surface energy and geometrically necessary dislocation (GND) content, but also on the properties of aggregates of grains such as grain boundary density.